2021
DOI: 10.1093/jn/nxab224
|View full text |Cite
|
Sign up to set email alerts
|

Iodine Nutrition and Iodine Supplement Initiation in Association with Thyroid Function in Mildly-to-Moderately Iodine-Deficient Pregnant and Postpartum Women

Abstract: Background Whereas the adverse effects of severe iodine deficiency during pregnancy are well documented, the effects of mild-to-moderate deficiency are not well established. Objectives We aimed to explore whether iodine nutrition and timing of iodine supplement initiation are associated with thyroid function in pregnant and postpartum women. Methods In this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…The majority of the plant-based milk alternatives that are on the rise in the Norwegian market are not iodine enriched ( 6 ). In Norway, mild to moderate iodine deficiency has been found among pregnant and lactating women ( 1 , 7 ) together with limited knowledge of iodine and health ( 8 10 ). Yet, little attention has been given to investigating young women’s attitudes toward milk, their milk consumption practices, and their knowledge about the potential health consequences of omitting milk from the diet ( 1 3 , 7 ).…”
Section: Popular Scientific Summarymentioning
confidence: 99%
“…The majority of the plant-based milk alternatives that are on the rise in the Norwegian market are not iodine enriched ( 6 ). In Norway, mild to moderate iodine deficiency has been found among pregnant and lactating women ( 1 , 7 ) together with limited knowledge of iodine and health ( 8 10 ). Yet, little attention has been given to investigating young women’s attitudes toward milk, their milk consumption practices, and their knowledge about the potential health consequences of omitting milk from the diet ( 1 3 , 7 ).…”
Section: Popular Scientific Summarymentioning
confidence: 99%
“…A 2021 observational study in China comparing women who took iodine supplements in preconception and pregnancy to those who did not found a positive effect on maternal T4 [52 ▪▪ ]. An observational study in Norway in a MMID area found MIS started in the preconception period had a similar beneficial effect with lower TSH and higher T3, T4 [53 ▪ ]. An RCT of 200 pregnant patients with MMID in Sweden found MIS to have a positive effect on maternal thyroglobulin and UIC, but not TSH or T4 [54 ▪▪ ].…”
Section: Iodine and Thyroid Functionmentioning
confidence: 99%
“…Three observational studies of I intake during pregnancy were completed in Norway. The first study in Norway assessed dietary I intake, UIC, and thyroid function in a cohort of pregnant women ( n = 1730) [ 79 ] during the 2nd and 3rd trimesters with I insufficiency by both UIC and dietary intake (94 μg/L and 85 μg/L and 202 μg/d and 153 μg/d, respectively) [ 79 ]. Among women taking an I-containing supplement before pregnancy and throughout pregnancy, TSH level was lower and T3 and T4 levels were higher than those not taking a supplement [ 79 ].…”
Section: Iodine and Thyroid Function In Pregnancymentioning
confidence: 99%
“…The first study in Norway assessed dietary I intake, UIC, and thyroid function in a cohort of pregnant women ( n = 1730) [ 79 ] during the 2nd and 3rd trimesters with I insufficiency by both UIC and dietary intake (94 μg/L and 85 μg/L and 202 μg/d and 153 μg/d, respectively) [ 79 ]. Among women taking an I-containing supplement before pregnancy and throughout pregnancy, TSH level was lower and T3 and T4 levels were higher than those not taking a supplement [ 79 ]. The study suggests that I intake can positively influence thyroid function in populations of pregnant women with mild-to-moderate I deficiency.…”
Section: Iodine and Thyroid Function In Pregnancymentioning
confidence: 99%